Tianhuang formula reduces the oxidative stress response of NAFLD by regulating the gut microbiome in mice - Luo, Duosheng; Yang, Ling; Pang, Huiting; Zhao, Yating; Li, Kunping; Rong, Xianglu; Guo, Jiao (Frontiers in Microbiology, 2022)
Background: Gut microbiomes affect the occurrence and development of NAFLD, but its mechanism has not yet been fully elucidated. Methods:The characteristics of the gut microbiome were representated by 16S rRNA sequencing, and the metabolites in intestinal contents and liver were discovered by non-targeted metabolomics. Correlation analysis and fermentation experiments revealed the relationship between the gut microbe and metabolites. Blood biochemical indicators, liver function indicators, and oxidation-related indicators were assayed. H&E staining and Oil Red O staining were used to analyze the characteristics of hepatic steatosis. RT-qPCR and western blotting were used to detect the expression of genes and proteins in liver tissues, and fecal microbial transplantation（FMT）was performed to verify the role of gut microbiome.Results:Gut microbiome especially Lactobacillus reduced, metabolites such as 5-Methoxyindoleacetate(5-MIAA) significantly reduced in liver and intestinal contents, the level of hepatic GSH, SOD reduced, MDA increased, and the protein expression of Nrf2 also reduced in NAFLD mice induced by high-fat diet (HFD). The normal diet mice transplanted with NAFLD mice feces showed oxidative liver injury, indicating that the NAFLD was closely related to gut microbiome. TH and TH-treated mice feces both can reshape the gut microbiome, increased the abundance of Lactobacillus and the content of 5-MIAA, improved oxidative liver injury. This indicated that the effect of TH improving NAFLD was related to gut microbiome especially Lactobacillus. 5-MIAA, produced by Lactobacillus was proved with fermentation experiments in vitro. Further experiments proved that 5-MIAA activated the Nrf2 pathway to improve the oxidative stress in NAFLD mice induced by HFD. TH reshaped the gut microbiome, increased the abundance of Lactobacillus and its metabolite 5-MIAA to alleviate oxidative stress and improved NAFLD.Conclusion:The studies have demonstrated a mechanism by which gut microbiome modulate oxidative stress in NAFLD mice induced by HFD. The traditional Chinese medicine TH improved NAFLD by regulating the gut microbiome, and its mechanism was related to the "Lactobacillus-5-MIAA-Nrf2" pathway. It provided a promising way for intervention of NAFLD.